THE EFFECTIVENESS OF LEAN SIX SIGMA IMPLEMENTATION IN HEALTH-CARE FACILITIES - Donn Kevinson Sondakh; Risty Mandane Laloan (Faculty of Economics and Business, Universitas Klabat, 2023)
This study was conducted to investigate the effectiveness of implementing Lean Six Sigma within the field of health care facilities. Lean Six Sigma is a powerful tool that can increase the organization performance. In this study A systematic review was performed in accordance with current best practices through close adherence to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. This study was found that the implementation of Lean Six Sigma enables the hospital to reduce the consumption of plasminogen by 69%, block utilization was increase by 13%-28%, book appointment increases by 24-276%, time saving were increase by 17% to 21%. And for service quality in blood collection was increased by 55% housewide. Lean Six Sigma is an inexpensive methodology to implement, it can bring many benefits to the organization in the health-care facilities. The successful implementation of Lean Six Sigma was able to reduce waste, reduce defect rate, increasing the quality of service, and reduce process variability that led to patient satisfaction and cost effective. Keywords: lean six sigma, health-care facility, productivity, efficiency